2012
DOI: 10.1159/000339034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Casein Kinase 1a Activator Pyrvinium Pamoate on Erythrocyte Ion Channels

Abstract: Pharmacological modification of protein kinase CK1 (casein kinase 1) has previously been shown to influence suicidal erythrocyte death or eryptosis, which is triggered by activation of Cl--sensitive Ca2+-permeable cation channels. Ca2+ entering through those channels stimulates cell membrane scrambling and opens Ca2+-activated K+-channels resulting in KCl exit and thus cell shrinkage. The specific CK1-inhibitor D4476 (1 µM) blunted, whereas the specific CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 0 publications
0
54
0
2
Order By: Relevance
“…Cells were then treated with ANG II (10 Ϫ7 M) for 16 h. An additional group of cells was treated with either an inhibitor of the Wnt signaling pathway (pyrvinium pamoate; 10 Ϫ9 M) or an AT1 receptor (candesartan; 10 Ϫ7 M) blocker. The dose of pyrvinium pamoate was based on previous studies showing its effectiveness at nanomolar concentrations in reducing ␤ catenin phosphorylation and proliferation in tumor cells (22,28,38,45). Additionally, it has been shown that pyrivinium pamoate selectively potentiates the casein kinase alpha activity with an EC 50 of 10 nM (45).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then treated with ANG II (10 Ϫ7 M) for 16 h. An additional group of cells was treated with either an inhibitor of the Wnt signaling pathway (pyrvinium pamoate; 10 Ϫ9 M) or an AT1 receptor (candesartan; 10 Ϫ7 M) blocker. The dose of pyrvinium pamoate was based on previous studies showing its effectiveness at nanomolar concentrations in reducing ␤ catenin phosphorylation and proliferation in tumor cells (22,28,38,45). Additionally, it has been shown that pyrivinium pamoate selectively potentiates the casein kinase alpha activity with an EC 50 of 10 nM (45).…”
Section: Methodsmentioning
confidence: 99%
“…Increased [Ca 2+ ] i further triggers phospholipid scrambling of the cell membrane with translocation of phosphatidylserine to the erythrocyte surface [15]. Signaling in the regulation of eryptosis includes in addition ceramide formation [15], caspase activation [17,18,19,20,21] and deranged regulation of several kinases such as AMP activated kinase AMPK [22], casein kinase 1α [23,24], cGMP-dependent protein kinase [25], Janus-activated kinase JAK3 [26], protein kinase C [27], p38 kinase [28], PAK2 kinase [29] as well as sorafenib [30] and sunitinib [31] sensitive kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Increased [Ca 2+ ] i triggers in addition phospholipid scrambling of the cell membrane with phosphatidylserine exposure at the erythrocyte surface [24]. Further triggers of eryptosis include ceramide formation [26], caspase activation [27,28,29,30,31] and deranged activities of AMP activated kinase AMPK [32], casein kinase 1α [33,34], cGMP-dependent protein kinase [35], Janus-activated kinase JAK3 [36], protein kinase C [37], p38 kinase [38], PAK2 kinase [39] sorafenib sensitive kinases [40] as well as sunitinib sensitive kinases [41]. …”
Section: Introductionmentioning
confidence: 99%